Stone residual fragments: A thorny problem. Issue 4 (November 2019) - Prezioso, Domenico; Barone, Biagio; Di Domenico, Dante; Vitale, Raffaele
Urolithiasis represents a widespread and common disorder among the world population, with a predicted increase in affected patients in the coming years. Treatment of renal and ureteral stones varies widely, and achieving true stone-free status in all patients is still difficult. Moreover, imaging used to assess residual fragments following procedure impacts the diagnosed stone-free rate percentage considerably. In particular, the use of computed tomography scans has led to a better evaluation of residual fragments as well as so-called clinically insignificant residual fragments, which in a considerable number of cases are, despite their definition, causes of adverse urological events, thus creating a thorny problem for both patients and urologists. Currently, there is no gold standard or validated protocol regarding the management, clearance and prevention of residual fragments. In this article, we review the current literature regarding residual fragments, clinically insignificant residual fragments and their natural history, reporting on diagnostic methods, incidence, complications and outcome with the use of less invasive procedures, taking into consideration viable treatment and management of patients affected.